Economic study of corn cob biomass as a boiler fuel substitution at PT XYZ in the animal feed industry - Alisharsa, Muhammad Dafa; Handayani, Wiwik (Journal of Applied Business Administration, 2026)
The use of biomass fuels such as palm kernel shells and candlenut shells has been implemented by the animal feed industry, but its energy consumption is still relatively high. This study aims to evaluate the feasibility of corn cobs as an alternative boiler fuel in reducing production costs. The method used is a quantitative descriptive approach with simulations through RETScreen software. The results show that the use of corn cobs combined with candlenut shells can produce energy savings, improve the economic value of the project NPV of 169,136 USD when converted to rupiah is obtained at Rp 2,748,460,000, IRR of 90,7%, payback period of 0.98 years (11 months), while the use of corn cobs combined with palm kernel shells produces NPV of 187,344 USD when converted to IDR is Rp 3,044,340,000, IRR of 105% and payback period of 1 year.